FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN MENJADI INVESTOR BARU SAHAM SYARIAH - Umam, Choirul; Aminullah Achmad Muttaqin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to find out what factors influence the decision to invest and become an investor in Islamic stocks during the Covid-19 pandemic. This study uses a quantitative approach with exploratory factor analysis method. The sampling method used was non-probability sampling with a purposive sampling technique with 105 samples obtained by distributing questionnaires to respondents who met the research criteria online. The results of this study reveal that there is an anomaly in new Islamic stock investors compared to old investors who tend to avoid investing during the Covid-19 pandemic. There are nine factors that influence the decision to invest and become new investors in Islamic stocks during the Covid-19 pandemic. These factors are technological advances, herding behavior, investment motivation, sharia compliance, risk perception, minimum investment capital, basic investment knowledge, avoiding speculation, and technical analysis factors.